Dependency of promiscuous soybean and herbaceous legumes on arbuscular mycorrhizal fungi and their response to bradyrhizobial inoculation in low P soils - Nwoko, H.; Sanginga, N. (1999)
As the production of grain and herbaceous legumes is often limited by low levels of available P in moist savanna soils, the potential for managing arbuscular mycorrhizal fungi (AMF) by selecting lines or accessions dependent on AMF as a strategy to improve plant P nutrition and productivity is required. The interactions between AMF and Bradyrhizobia sp. and their effects on growth and mycorrhizal colonization of ten recent selections of promiscuous soybean breeding lines and two herbaceous legumes (Lablab purpureus and Mucuna pruriens) were investigated. The pots contained soil (available P = 5.33 mg P soilÿ1 , Bray 1) collected at Fashola from a derived savanna in Nigeria. Mycorrhizal colonization differed among promiscuous soybean lines (ranging from 16 to 33%) and was on average 20% for mucuna and lablab. Shoot weight of plants single or dually inoculated with AMF and Bradyrhizobia sp. were higher than those of uninoculated plants and the differences between lines and species were signi®cant. Three groups of plants were obtained according to their mycorrhizal dependency (MD): (i) the highly dependent plants with (MD) >30%, e.g.,soybean line 1039 and mucuna; (ii) the intermediate group, with MD between 10 and 30%, e.g., soybean line 1576 and lablab, and (iii) the majority of soybean lines (®ve lines out of 10) that were not mycorrhizal dependent. This great variability in MD and response to P application among promiscuous soybean and herbaceous legumes offers a potential for the selection of plant germplasm able to grow in P de®cient soil. # 1999 Elsevier Science B.V. All rights reserved.